2013
DOI: 10.1152/ajpendo.00114.2013
|View full text |Cite
|
Sign up to set email alerts
|

Marked phenotypic differences of endurance performance and exercise-induced oxygen consumption between AMPK and LKB1 deficiency in mouse skeletal muscle: changes occurring in the diaphragm

Abstract: O. Marked phenotypic differences of endurance performance and exercise-induced oxygen consumption between AMPK and LKB1 deficiency in mouse skeletal muscle changes occurring in the diaphragm. Am J Physiol Endocrinol Metab 305: E213-E229, 2013. First published May 21, 2013; doi:10.1152/ajpendo.00114.2013.-LKB1 phosphorylates members of the AMP-activated protein kinase (AMPK) family. LKB1 and AMPK in the skeletal muscle are believed to regulate not only fuel oxidation during exercise but also exercise capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
(80 reference statements)
7
9
1
Order By: Relevance
“…Our findings agree with those of Miura, et al (33), who very recently showed a similar impairment in exercise tolerance in a skmLKB1-dominant negative mice. Ambulatory cage activity, however, was not altered in skmLKB1-KO mice, indicating that differences between genotypes in untrained mice are not due to a chronic decrease in physical activity.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings agree with those of Miura, et al (33), who very recently showed a similar impairment in exercise tolerance in a skmLKB1-dominant negative mice. Ambulatory cage activity, however, was not altered in skmLKB1-KO mice, indicating that differences between genotypes in untrained mice are not due to a chronic decrease in physical activity.…”
Section: Discussionsupporting
confidence: 94%
“…AMPK␣1 activity, on the other hand, was not significantly reduced vs. CON muscle in untreated or AICAR-treated skmLKB1-KO muscles. Our findings are consistent with previous findings from mLKB1-KO mice (25) and with very recent data from skeletal muscle-specific LKB1-dominant negative (skmLKB1-DN) mice (33). The persistent AMPK␣1 activity in skmLKB1-KO muscle is likely due to 1) the presence of nonskeletal muscle cells (endothelial cells, neurons, adipocytes) in the tissue sample that highly express AMPK␣1 and do not lack LKB1 and 2) the potential presence of an alternate AMPK kinase, such as calcium/calmodulindependent protein kinase kinase (CaMKK), that is able to phosphorylate AMPK in the absence of LKB1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Studies conducted in different mouse models with a functional ablation of the AMPKα2 subunit have not shown any genotype differences in RER during exercise or in ex vivo contraction‐induced FA oxidation (13, 1518). While 2 of these studies observed that the RER was increased with exercise in LKB1‐deficient models, it led to the conclusions that LKB1 but not AMPK is involved in regulating FA oxidation in mouse skeletal muscle with exercise (17, 18). This suggests that exercise‐ and contraction‐induced FA utilization in skeletal muscle is compromised only when either LKB1 or both AMPKα1 and AMPKα2 protein expression is ablated, reinforcing the role of the LKB1‐AMPKα axis in metabolic regulation with exercise and muscle contraction.…”
Section: Discussionmentioning
confidence: 99%